The changing tradition : women in the history of rhetoric - Sutherland, Christine Mason; Sutcliffe, Rebecca J. (Rebecca Jane), 1963- (University of Calgary Press, 1999)
This collection of essays is the culmination of recent scholarship on the relationship of women to the rhetorical tradition, something which, for centuries, excluded them. Contributors to this timely volume include scholars from all across North America, Europe and Australia, and their work clearly demonstrates contemporary feminist modes of investigating traditional rhetorics.